2015
DOI: 10.1080/07373937.2015.1025907
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Analysis on a Lignite-Fired Power System Integrated with a Steam Dryer: Investigation on Energy Supply System of the Dryer

Abstract: Lignite is becoming a competitive fuel for power generation with high security of supply and a low price. But a power plant firing lignite directly always has some weaknesses, including low thermal efficiency and high construction investment. That pre-drying lignite before feeding it to the boiler is a potential method to tackle these weaknesses, and low pressure steam extracted from steam turbines is considered as a competitive heat source for the drying process. In a lignite-fired power system integrated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Fault Level = • (4) in which = • , is the nominal voltage of converter bus, is ground impedance, and is the nominal power delivered by dc system. Commutation failure is a random event, and we must grasp the statistical magnitude that reflect CF essence to know about the random event [3] . For each fault level, the probability of CF is calculated as the fraction of faults of a total of 100 applied at different points on wave within a cycle that resulted in CF [4] .…”
Section: Fig 4 Anomalous Cf In Double-infeed Systemmentioning
confidence: 99%
“…Fault Level = • (4) in which = • , is the nominal voltage of converter bus, is ground impedance, and is the nominal power delivered by dc system. Commutation failure is a random event, and we must grasp the statistical magnitude that reflect CF essence to know about the random event [3] . For each fault level, the probability of CF is calculated as the fraction of faults of a total of 100 applied at different points on wave within a cycle that resulted in CF [4] .…”
Section: Fig 4 Anomalous Cf In Double-infeed Systemmentioning
confidence: 99%
“…Han et al [9] showed that power plant efficiency could be increased by 1.51% using flue gas drying with waste heat recovery. Liu et al [10] proposed using a compressor or ejector to enhance the performance of a steam drying system. Xu et al [11] proposed using a supplementary steam cycle to improve the performance of a steam dryer in a power plant.…”
Section: Introductionmentioning
confidence: 99%
“…Lignite upgrading technologies, including pre-drying and pyrolysis, are effectively to improve lignite utilization efficiency. Therefore, many researches were conducted for the lignite pre-drying [2,3,4] and pyrolysis [5,6] technologies. However, these two technologies are isolatedly used.…”
Section: Introductionmentioning
confidence: 99%